1998
DOI: 10.2337/diacare.21.4.597
|View full text |Cite
|
Sign up to set email alerts
|

Outcome Results of the Fosinopril Versus Amlodipine Cardiovascular Events Randomized Trial (FACET) in Patients With Hypertension and NIDDM

Abstract: Fosinopril and amlodipine had similar effects on biochemical measures, but the patients randomized to fosinopril had a significantly lower risk of major vascular events, compared with the patients randomized to amlodipine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
389
1
30

Year Published

1998
1998
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 764 publications
(426 citation statements)
references
References 0 publications
6
389
1
30
Order By: Relevance
“…For this reason, a first-ever-event analysis could have been helpful to correctly interpret the ABCD results, but was not presented. 18 In the Fosinopril versus Amlodipine Cardiovascular Events Randomized Trial (FACET), 17 the patients receiving fosinopril had a significantly lower risk of the combined outcome of acute myocardial infarction, stroke, or hospitalized angina pectoris than those receiving amlodipine (14/189 vs 27/191 events). However, the FACET trial had an open design and events were monitored by 'asking' the patients if they had been hospitalized or had experienced any other event.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For this reason, a first-ever-event analysis could have been helpful to correctly interpret the ABCD results, but was not presented. 18 In the Fosinopril versus Amlodipine Cardiovascular Events Randomized Trial (FACET), 17 the patients receiving fosinopril had a significantly lower risk of the combined outcome of acute myocardial infarction, stroke, or hospitalized angina pectoris than those receiving amlodipine (14/189 vs 27/191 events). However, the FACET trial had an open design and events were monitored by 'asking' the patients if they had been hospitalized or had experienced any other event.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the ABCD trial, 18 the worse outcome on amlodipine compared with the converting-enzyme inhibitor was not due to myocardial infarction (13 vs 10), but was driven by hospitalized angina (4 vs 0) and stroke (10 vs 4). The interpretation of the FACET results 17 is also rendered difficult, because 58 patients randomised to fosinopril (30.7%) and 50 of the amlodipine group (26.2%) crossed over and received the combination of both drugs. A recent subgroup analysis of the Syst-Eur trial 29 showed that in patients with diabetes mellitus active treatment reduced all-cause mortality by 55%, cardiovascular mortality by 76%, all cardiovascular end-points by 69%, fatal and nonfatal stroke by 73% and all cardiac end-points by 63%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…14 In this open labelled study that randomised participants to either an ACE inhibitor or a long acting dihydropyridine CCA, the cardiac event rate was approximately double in the amlodipine alone group vs the ACE inhibitor group. Moreover, the trial was stopped early due to this trend.…”
mentioning
confidence: 99%